IMPROVING THE QUALITY OF TEMPE PRODUCTS USING THE IMPLEMENTATION METHOD OF GOOD MANUFACTURING PRACTICE (GMP) AND MODEL BASED AND INTEGRATED PROCESS IMPROVEMENT (MIPI) IN TEMPE SROMO SMEs - ananda (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2022)
Mr. Muizzi's Tempe Sromo UKM is one of the largest Tempe UKM in Sromo. However, SMEs (Small and Medium Enterprises) Tempe Sromo in the production process do not pay attention to environmental cleanliness so that it affects the quality of the tempe products produced. Therefore it is necessary to carry out a Good Manufacturing Practice (GMP) assessment which aims to provide a concept of proposed improvements using the Model Based and Integrated Improvement (MIPI) method as an effort to improve the quality of the products produced. Based on the results of the Good Manufacturing Practice (GMP) assessment of Mr. Muizzi's Tempe Sromo, the overall value of the total application of GMP for all respondents obtained is 8145 points or an average of 247 points per respondent, while the percentage of deviation value is 46% and the value 54% conformity to the aspects of Good Manufacturing Practice (GMP) in Mr. Muizzi's Tempe East Sromo UKM which means that it does not meet the GMP criteria. Evaluation obtained from processing GMP data, the level ofseverity in the application of Good Manufacturing Practice (GMP) to Mr. Muizzi's Tempe Sromo SME which is 247 points, which means that it is at the classification level ((nx2) +1) to (nx3), which is very high. less fulfilling. The highest deviation value in the top five is in the laboratory aspect with a deviation value of 73%, 68% label, 49% storage, 48% building, and aspects of sanitation facilities with the aspect of production equipment getting the same deviation value of 47%.